Endoscopic third ventriculostomy for shunt malfunction: What to do with the shunt? - Neils, David M. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Endoscopic third ventriculostomy (ETV) is an effective surgical option for the treatment of shunt malfunction. The role of postoperative cerebrospinal fluid (CSF) diversion is not clearly understood at this time. We compare the effects of shunt-removal/ligation, shunt externalization or external ventricular drain placement, and no treatment to the indwelling shunt at the time of ETV. METHODS: We retrospectively reviewed the records of 20 consecutive patients treated at our institution for shunt malfunction with ETV. Patient data were retrospectively evaluated for the effect that the fate of the shunt plays on ETV success rates. RESULTS: In our series of 20 patients we had an overall success rate of 70% with using ETV for shunt malfunction. Patients who had their shunts ligated at the time of surgery had a success rate of 88%, in comparison to those whom the shunt was left untouched who had a success rate of 60%, or patients who had a perioperative external ventricular drain placed the success rate was 50%. CONCLUSIONS: This series of ETV for shunt malfunction performed at a single center by a single surgeon shows a success rate similar to the published literature range of 67 to 80 percent success whether the shunt is ligated or left undisturbed. It is not necessary to ligate the in situ shunt at the time of ETV; however, there may be a trend toward an improved success rate with shunt ligation. Further studies with a greater numbers of patients are warranted.